Traditions in Motion: Paolle Dance and Symbolic Identity Construction of Bantaeng Mountain Communities, South Sulawesi, Indonesia - Fifie Febryanti Sukman; Fitra Airiansyah (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2026)
Paolle Dance is one of the traditional performing arts of the mountain communities in Bantaeng Regency, South Sulawesi, which serves not only aesthetic functions but also social, spiritual, and symbolic ones. This article examines how Paolle Dance constructs and represents the symbolic identity of indigenous communities through its performance structure, movement symbols, music, costumes, and social context. This type of research is qualitative with a dance ethnography approach (ethnochoreology). In explaining this phenomenon, the study draws on ethnochoreological perspectives as developed by Kaeppler and symbolic anthropology as proposed by Geertz, which emphasize dance as a system of meaning embedded in social and cultural practices. Data were collected through participatory observation, in-depth interviews, and field documentation. The results show that Paolle Dance plays an important role in maintaining social and spiritual harmony through traditional rites, serving as an arena for articulating collective identity, and performing regulative functions within the community. Symbolic elements in the performance, such as body movements, traditional musical instruments, and costume attributes, carry deep meanings linked to the community's cosmology and social structure. Amid cultural change and expansion, Paolle Dance undergoes adaptation while maintaining its core values through symbolic resistance by the indigenous community. This study concludes that Paolle Dance is a living cultural expression that actively shapes, maintains, and negotiates the identity of mountain communities in changing local and global contexts. Theoretically, this study contributes to the development of ethnochoreological and symbolic anthropological perspectives by providing empirical evidence of how traditional dance functions as a dynamic system for constructing and sustaining cultural identity.